Respiratory system parameters in children with low severity cystic fibrosis: is there early involvement in relation to healthy peers? - Gabriela Castilhos Ducati; Juliana Cardoso; Elaine Paulin Ferrazeane; Camila Isabel Santos Schivinski (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To compare and analyze pulmonary function and respiratory mechanics parameters between healthy children and children with cystic fibrosis. Methods: This cross-sectional analytical study included healthy children (HSG) and children with cystic fibrosis (CFG), aged 6-13 years, from teaching institutions and a reference center for cystic fibrosis in Florianópolis/SC, Brazil. The patients were paired by age and sex. Initially, an anthropometric evaluation was undertaken to pair the sample characteristics in both groups; the medical records of CFG were consulted for bacterial colonization, genotype, and disease severity (Schwachman-Doershuk Score - SDS) data. Spirometry and impulse oscillometry were used to assess pulmonary function. Results: In total, 110 children were included, 55 in each group. In the CFG group, 58.2% were classified as excellent by SDS, 49.1% showed the ΔF508 heterozygotic genotype, and 67.3% were colonized by some pathogens. Statistical analysis revealed significant differences between both groups (p<0.05) in most pulmonary function parameters and respiratory mechanics. Conclusions: Children with cystic fibrosis showed obstructive ventilatory disorders and compromised peripheral airways compared with healthy children. These findings reinforce the early changes in pulmonary function and mechanics associated with this disease.